PENERAPAN MODEL NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPS PESERTA DIDIK KELAS VI SD - renda Lestari; Willyan Saputra (LP3M Universitas Muhammadiyah Muara Bungo, 2020)
The problem in this study is the learning process and learning outcomes of students in social studies learning in Class VI SD Negeri 81/II Muara Bungo is still low, this is evidenced by the results of preliminary observations made by researchers of 37 students only only 7 students (18.91%) who obtained value in the completion criteria. The reason is that teachers only use conventional approaches in the classroom, which causes the learning process and student learning outcomes to be low. The subjects of this study were students of class VI of SD 81/II Muara Bungo, amounting to 37 students. In the implementation of this study consisted of two cycles carried out by researchers. Each cycle consists of planning activities, implementation accompanied by observation and reflection in each cycle. This study aims to describe the application of the NHT model in improving the process and learning outcomes of social studies in SD Negeri 81/II Muara Bungo classes. The research data was collected through observation, documentation and test results. The results of the analysis of the research data indicate that the use of the NHT model can improve social studies learning outcomes of Class VI SD Negeri 81/II Muara Bungo. This can be seen from the results of the second cycle students' tests have reached KKM 75, seen in the learning outcomes of completeness of the learning outcomes of the first cycle is 29.72% in the second cycle increased to 83.78%.